Identification of structural parameters of multistorey shear buildings from modal data. - Chakraverty, S. (Earthquake engineering & structural dynamics.)
A procedure has been presented in this paper to identify the structural parameters, viz. mass and stiffness matrices, from modal test data for multistorey shear buildings. The first two orders of modal data have been used by other researchers to estimate the global matrices where they depend on measurable points which are less than the total number of structural degrees of freedom. The above method has been refined here by using Holzer criteria along with other numerical methods to estimate the global mass and stiffness matrices of the structure. This shows the methodology to be more efficient and accurate. The reliability of the procedure has been shown by examples of multistorey buildings.